Regularities of spring runoff formation and erosion under the influence of forest and agrotechnical rec-lamation in the southern chernozem of the Volga region. Issue 3 (March 2021) - Proezdov, Peter; Eskov, Dmitry; Rozanov, Alexander; Sviridov, Sergey
Abstract: The purpose of the study was to determine the regularities of the spring formation elements of water balance and soil erosion under the influence of a set of anti-erosion techniques based on long-term observations (1964-2020). The research object was created in 1964 on the land of the farm "Vyazovsky". The complex of anti-erosion techniques consists of two forest strips 300 m apart, reinforced with ditches. The inter-lane space was developed by crop rotations and pasture with the use of mulched crevices to combat, with silting and ice content of cracks. The dose of straw sections at a distance between the slits of 1.4 m – 4.8 t / ha. Forest belts accumulate snow by 33.3% more than open agricultural landscapes, and in low-snow winters, the effect of snow deposition increases by another 20%. Long-term studies of spring runoff on land in the steppe of the Volga upland allowed us to recommend the appropriate values of 10% probability of excess for creating soil protection complexes from erosion: moldboard ploughland – 25 mm, moldboardless ploughland– 47 mm, winter crops и grass pastures – 65 mm. The content of southern chernozem with A+B <0.5 m at the permissible level of erosion equal to 0.3 t / ha is possible when a complex of anti-erosion forest reclamation and agrotechnical techniques is introduced into the technology of crop cultivation. Regression and correlation analysis found that the spring runoff coefficient and spring soil erosion depend on the amount of water reserves in the snow and the degree of protection of land from erosion by anti-erosion techniques by 92-99%.